ChemInform Abstract: Concise Total Synthesis of (+)‐Asperazine, (+)‐Pestalazine A, and (+)‐iso‐Pestalazine A. Structure Revision of (+)‐Pestalazine A. Issue 29 (29th June 2016) - Loach, Richard P.; Fenton, Owen S.; Movassaghi, Mohammad
Abstract: The enantioselective total syntheses of (+)‐asperazine (Ia), (+)‐iso‐pestalazine A (Ib), and (+)‐pestalazine A (Ic) are completed in 11 steps from commercial N‐Boc‐L‐tryptophan methyl ester, in overall yields 6.8%, 8.0% and 4.8%, resp.